Effect of BCG accination on cytokine mRNA expression in atopic children with asthma - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
Background: To inestigate whether a preexisting TH2-type immune response could be suppressed by BCG immunization in atopic children with asthma. Methods and results: We hae used PCR to amplify reerse transcribed RT IFN- and IL-5 mRNA expressed by peripheral blood mononuclear cells PBMCs in response to in itro phytohemagglutinin A, purified protein deriatie and Dermatophagoides pteronyssinus II stimulation from nine atopic children, both before and 8 weeks after BCG accination. We hae demonstrated that IFN- expression was induced in response to all stimulants IFN-actin after the accination, whereas there was no expression before P<0.001. Although there was a tendency to diminish in the expression of IL-5 mRNA in response to the stimulants, only PHA rendered a statistically significant decrease after the accination. Conclusions: These results proide some eidence of TH1 dominance after BCG administration in atopic children. 2002 Elseier Science B.V. All rights reserved.
Keywords: BCG; atopy; asthma; CALMETTE-GUERIN; MICE; INTERLEUKIN-12; INFECTION; OVALBUMIN; VACCAE